Catalytic stripping voltammetric determination of vanadium in the presence of chloranilic and bromate - Bobrowski, Andrzej; Nowak, Katarzyna; Zarębski, Jerzy (Univerzita Pardubice, 2006)
A catalytic system, vanadium - chloranilic acid and bromate was investigated by adsorptive stripping voltammetry by means of hanging mercury electrode as well as bismuth film electrode. At the optimal conditions, 0.1 M acetic buffer, pH 4.8, 3.0 x 10-5 M CAA, 1.0 x 10-2 M KBrO3, accumulation potential -0.15 V and accumulation time 100s, the detection limit was found to be 9.0x10-12 M of V(V) on hanging mercury electrode. The results obtained on bismuth film electrode are also presented.
Keywords: stripping voltametrie; katalytické procesy; vanad; stanovení; adsorptivní rozpouštěcí voltametrie